The effect of Teaching Methods and Learning Styles on Students’ Achievement in Reading Comprehension - Parwati Parwati; Busmin Gurning; Berlin Sibarani (LINGUISTIK TERAPAN, 2014)
The objectives of this experimental research were to investigate whether: 1) students’ achievement in reading comprehension taught by using CIRC method was higher than taught by using Jigsaw method. 2) students’ achievement in reading comprehension with visual style was higher than those with kinesthetic style, 3) there was interaction between teaching methods and learning styles on students’ achievement in reading comprehension. One hundred of 2011/2012 grade X students of SMAN 1 Delitua were selected as sample by applying cluster random sample technique. The research design was experimental research by using factorial design 2x2. Experimental group 1 was treated by using CIRC method and experimental group 2 was treated by using Jigsaw method. The questionnaire was conducted for classifying the students upon the visual and kinesthetic learning style. Students’ achievement in reading comprehension text was measured by using reading comprehension test. The data were analyzed by applying two-way analysis of variance (ANOVA) at the level of significance α= 0.05. The result reveals that (1) students’ achievement in reading comprehension taught by using CIRC was higher than that taught by using Jigsaw method, with Fobs= 3.36>Ftab=2.70, (2) students’ achievement in reading comprehension with visual learning style was higher than that with kinesthetic learning style with Fobs= 8.64>Ftable=2.70, (3) there is interaction between teaching method and learning styles on students’ achievement in reading comprehension with Fobs=7.74>Ftable=2.70. The result of Scheffe-Test showed that visual style students got higher achievement if they were taught by using CIRC method while kinesthetic style students got higher achievement if they were taught by using Jigsaw method.